Integrating Fuzzy Logic Technique in Case-Based Reasoning for Improving the Inspection Quality of Software Requirements Specifications - Mostafa S.A.; Gunasekaran S.S.; Khaleefah S.H. (Springer, 2023)
Computer circuits; Engineering research; Formal specification; Fuzzy logic; Inspection; Requirements engineering; Case-base reasonings; Fuzzy logic techniques; Inspection quality; Matching process; Quality inspection; Reasoning framework; Similarity measurements; Software requirements specifications; Case based reasoning